CCNA Cyber Ops SECFND 210-250 : complete video course - Santos, Omar (LiveLessons (Indianapolis, Ind.), 2017)
CCNA Cyber Ops SECFND 210-250 LiveLessons is a unique video product that provides a solid understanding of the key areas of knowledge required to pass the 210-250 SECFND exam. This product walks through each topic of the exam blueprint, so you can gain the knowledge you need to pass the exam and start your career as an associate-level Security Operations Center (SOC) Security Analyst. CCNA Cyber Ops SECFND 210-250 contains more than nine hours of instruction with 12 lessons. The videos consist of live video training, video screencasts, and demos. Video instruction throughout offers detailed explanations, tips, and design recommendations.